2018
DOI: 10.1080/10428194.2018.1516036
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patients with acute myeloid leukemia and high-risk myelodysplastic syndrome treated on versus off study

Abstract: Patients with newly diagnosed (ND) and relapsed/refractory (RR) acute myeloid leukemia (AML) and high-risk myelodysplastic syndrome (MDS, ≥10% blasts) often receive intensive chemotherapy at diagnosis and relapse. We retrospectively identified 365 patients and categorized the reasons for receiving treatment off study (medical, logistical, or unclear). The pre-treatment characteristics of the on and off study groups were similar. Rates of complete remission (CR) without measurable residual disease were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Our finding that ineligibility is associated with decreased survival suggests that standard clinical trial criteria may identify a population of patients with better outcomes following treatment; improved responses and survival have also been demonstrated in an “on study” population when the same induction regimen was administered to patients both on and off clinical trial at our center and in a national population-based cohort study from Denmark. 17 , 18 These findings contrast some with the Statler analysis of AML patients, which did not identify significant differences in response or survival based on comorbidities other than liver disease and organ dysfunction. 6 In the future, evaluation of other factors including travel distance, social support, and frailty level could provide a more nuanced picture of eligibility.…”
Section: Discussioncontrasting
confidence: 62%
“…Our finding that ineligibility is associated with decreased survival suggests that standard clinical trial criteria may identify a population of patients with better outcomes following treatment; improved responses and survival have also been demonstrated in an “on study” population when the same induction regimen was administered to patients both on and off clinical trial at our center and in a national population-based cohort study from Denmark. 17 , 18 These findings contrast some with the Statler analysis of AML patients, which did not identify significant differences in response or survival based on comorbidities other than liver disease and organ dysfunction. 6 In the future, evaluation of other factors including travel distance, social support, and frailty level could provide a more nuanced picture of eligibility.…”
Section: Discussioncontrasting
confidence: 62%
“…Although the authors adjusted their multivariable analysis for known risk factors for an adverse outcome such as age and IPSS‐R risk group, other confounders such as comorbidities and the rate of therapy‐related MDS were not captured in the analysis, and this limits the interpretation of the finding 13,17 . Although it is also possible that outcomes for patients enrolled in clinical trials are superior because of potentially closer monitoring as part of the clinical trial as well as benefits of the trial regimens themselves, differences in baseline patient characteristics and trial enrollment have been shown in patients with acute myeloid leukemia treated on and off trial as well and are likely to explain the mortality benefit for patients treated on trial 18 . However, the fact that patients enrolled in clinical trials differ substantially in terms of social determinants of health is a worrisome finding that is also seen in other cancer trials, and efforts to improve outcomes for all patients are warranted 19 …”
Section: Figurementioning
confidence: 99%
“…13,17 Although it is also possible that outcomes for patients enrolled in clinical trials are superior because of potentially closer monitoring as part of the clinical trial as well as benefits of the trial regimens themselves, differences in baseline patient characteristics and trial enrollment have been shown in patients with acute myeloid leukemia treated on and off trial as well and are likely to explain the mortality benefit for patients treated on trial. 18 However, the fact that patients enrolled in clinical trials differ substantially in terms of social determinants of health is a worrisome finding that is also seen in other cancer trials, and efforts to improve outcomes for all patients are warranted. 19 With an annual age-adjusted incidence rate of 4 per 100,000 persons in the United States, MDS is a rare disease, and clinical trial recruitment requires concerted efforts.…”
mentioning
confidence: 99%